Addressing the requirements of costume design for selected UP Repertory stage plays - Alcantara, Carmaela B.; Rayala, Ma. Monica Escano (Quezon City College of Home Economics, University of the Philippines Diliman, 2011)
ABSTRACT This study sought to evaluate costume designs as they relate to the requirements of three stage plays of the UP Repertory Company. This case study aimed to identify the different ways that costume designers of the UP Repertory Company undertake in addressing the requirements of a play. The need to further understand the actual practices of costume designers for local plays directed the researcher in undertaking this study. The UP Repertory Company, a theater group that has done several plays, was interviewed to investigate the approaches undertaken by their costume designers in conceptualizing costumes for different stage plays. Secondary information from books, theses, articles from the internet and newsletters, and sketches of costume designs were used. Results show that the requirements of costume design include the objective and the style of the play, costume research, characterization, available materials, budget, and prerequisites of the script. Moreover, it was found that the costume designer decides which of these needs are to be given most importance, depending on the needs of the play. Only the requirements, which the designer deems necessary, are addressed in order to maximize resources. This study is helpful in understanding costume design further as it identified and described the requirements of local plays. It also provided more information on how costume designers address these requirements through designs of costumes. Furthermore, it promotes the appreciation of costume design as an important element of stage plays.
Thesis (B.S.Clothing Technology)--University of the Philippines Diliman.
Keywords: Costume design -- Philippines; Costume -- Philippines